Axial anomaly in galaxies and the dark universe - Meinert, Janning; Hofmann, Ralf (Universe, 2021)
Motivated by the SU(2)CMB modification of the cosmological model ΛCDM, we consider isolated fuzzy-dark-matter lumps, made of ultralight axion particles whose masses arise due to distinct SU(2) Yang-Mills scales and the Planck mass MP. In contrast to SU(2)CMB, these Yang-Mills theories are in confining phases (zero temperature) throughout most of the Universe’s history and associate with the three lepton flavours of the Standard Model of particle physics. As the Universe expands, axionic fuzzy dark matter comprises a three-component fluid which undergoes certain depercolation transitions when dark energy (a global axion condensate) is converted into dark matter. We extract the lightest axion mass ma,e=0.675×10−23 eV from well motivated model fits to observed rotation curves in low-surface-brightness galaxies (SPARC catalogue). Since the virial mass of an isolated lump solely depends on MP and the associated Yang-Mills scale the properties of an e-lump predict those of μ- and τ-lumps. As a result, a typical e-lump virial mass ∼6.3×1010M⊙ suggests that massive compact objects in galactic centers such as Sagittarius A* in the Milky Way are (merged) μ- and τ-lumps. In addition, τ-lumps may constitute globular clusters. SU(2)CMB is always thermalised, and its axion condensate never has depercolated. If the axial anomaly indeed would link leptons with dark matter and the CMB with dark energy then this would demystify the dark Universe through a firmly established feature of particle physics.